'The Shadow in the East': Representations of the Russo-Japanese war in newspaper cartoons. Issue 3 (2nd October 2017) - Williams, Chris
Abstract : The Russo-Japanese War of 1904–1905 captured the imagination of reading publics around the world and in Britain spawned a breadth of products aimed at a domestic audience, including cigarette cards, illustrated magazines and newspaper cartoons. This essay investigates the commentary on and interpretation of the war offered by cartoons appearing in the British Sunday paper the News of the World and the Welsh daily paper the Western Mail . Editorial cartoonist J. M. Staniforth drew over 70 cartoons documenting the war for both papers, and the degree to which these visual images complemented or diverged from the editorial line expressed in leader columns is considered. The importance of distinguishing between cartoons and editorials and of taking into account the identity and career of the cartoonist is stressed. The visual codes for communicating conflict are also investigated, revealing in the process something of the intellectual horizons of both cartoonist and audience.